Mitigation of salinity-induced adverse effects through exogenous application of gibberellic acid in turnip (Brassica rapa L.) - Ambreen Fatima; Shaheena Umbreen; Sehrish Sadia; Muhammad Waheed; Fahim Arshad; Muhammad Raza Malik; Abeer Hashem; Ajay Kumar; Elsayed Fathi Abd_Allah (Cogent Food & Agriculture)
Soil salinity is the primary factor restricting plant growth and development. In this study, the morpho-physiological, biochemical, and molecular responses of turnip seedlings to three distinct salt stress treatments were investigated: no salinity 0 mM, moderate salinity at 80 mM, and severe salinity at 160 mM. Gibberellic acid treatments were applied in three different concentrations: control, 1 mM, and 2 mM. The dry and fresh weights, shoot and root lengths, carotenoid and chlorophyll levels, K+ ion accumulation, and antioxidant enzyme activity were all decreased by salt stress, particularly at 200 mM. However, it accelerated the buildup of Na+ ions and oxidative damage. Application of gibberellic acid enhanced turnip development under salt stress. Compared with the control, the gibberellic acid-2mM recorded the highest increase in roots and shoots length (16.79–10.80%), shoots fresh and dry weights (15.21–28.39%), chlorophyll a and b (7.49–15.94%), SOD and POD (16.92–10.85%), yield weight and diameter (18.33–10.11%) during different salinity levels. This treatment also reduced the MDA and H2O2 content (15.12–10.58%), and Na+ ions in roots and leaves (20.20–5.44%). Based on these findings, gibberellic acid at a concentration of 2 mM may be a useful tool for enhancing turnip development and growth.